Unusual Presentation of Metallic Foreign Body Aspiration after Penetrating Neck Trauma - Reza Bagheri; Reza Afghani (Journal of Cardio-Thoracic Medicine, 2013)
A 25 year-old Construction worker underwent neck laceration following penetrating neck trauma in a falling incident. The 3rd tracheal ring was injured which was initially repaired and the patient was discharged in good general condition. (Figure 1 shows the patient’s neck view after discharge from hospital).Two months later the patient was again admitted due to provocative coughing and a metal foreign body was detected in his right main bronchus. (Figure 2 shows CXR of the patient and Figure 3 demonstrates CT scan of the same patient). Finally the patient underwent rigid bronchoscopy to remove the foreign body. (Figure 4 shows the foreign body after rigid bronchoscopy).